Effect of ß-xilanase and ß-glucanace supplementations on the performances of broiler chickens - I.A.K Bintang; A.P Sinurat; P.P Ketaren (Indonesian Center for Animal Research and Development (ICARD), 2006)
A study was conducted to evaluate the effect of enzyme supplementation on the performances of broiler chickens. One hundred and twenty five day old chicks (DOC) were allocated into five dietary treatment with 5 replicates. Every replicate had 5 DOC. The treatments were: control, control + 0.02% ß-xylanase, control + ß glucanase at three levels (0.05; 0.10 and 0.20%). The treatments were carried out in a randomized block design. Parameter measured were: feed intake, live weight gain and feed conversion ratio (FCR) at 3 and 5 weeks old, while carcass, internal organ, abdominal fat, thickness of intestine, and mortality were observed only at 5 weeks old. The results showed that enzyme supplementation did not significantly (P>0.05) affect feed intake and live weight gain of chicks at 3 weeks old, but the FCR of enzyme supplementation was significantly (P<0.05) better as compared with the control. FCR of birds fed with ß-glucanase tended to be better than the ß-xylanase supplementation (P>0.05). The enzyme addition did not significantly (P>0.05) affect all parameters recorded at 5 weeks old chickens. It is concluded that the best treatment for chicks at 3 weeks old was 0.05% ß-glucanace supplementation. This treatment improved 7.55% FCR as compared to the control. Key Word: Enzyme, Performances, Broiler